Social rehabilitation in gender-based violence matters (Legal journal - Research in Legal and Social Sciences, 2020)
The present research covers the criminal politics on gender-based violence matters in the spanish legislation, taking as a starting point the Organic Act number 1/04 “Full protection against gender-based violence”. The enacment of the Act appears as the result of several amendments of the spanish Penal Code regarding the common description of psysichal violence within the family, where women are the main victims. In this respect, most of the authors claim that violence against women arises from the historical structural inequality between men and women. For this reason, it is important to conduct a comprehensive comparative study of the paraguayan criminal politics in contrast with the spanish, in view of the recent enactment of the Act number 5777/16 “Full protection for women against all forms of violence”, that enables to describe wether the mechanism set out in the mentioned Act are factible for the sake of the offeder's social rehabilitation, or if the education is the best way to rehabilitate offenders, whenever it is a gender-based violence case.
Keywords: gender-based violence; social rehabilitation; education; criminal politics